Three Common Genetic Variants Predict Type 2 Diabetes - Gater, Laura (MD Conference Express, 2006)
Prospective studies of genetic risk for disease are difficult to conduct but can yield unique information on the risk of developing a chronic disease. A group from Sweden undertook a very ambitious project: to prospectively follow over 7,000 adults in order to explore genetic predictors of the development of type 2 diabetes. This article presents data from this group of patients who have been followed for 22 years.